The nexus of big data analytics, knowledge sharing, and product innovation in manufacturing - Bülent Yildiz; Şemsettin Çiğdem; Ieva Meidutė-Kavaliauskienė; Renata Činčikaitė (Journal of Business Economics and Management, 2024)
In today‘s highly competitive business environments, manufacturers face stiff competition. As digital technologies have become more pervasive, many businesses in the manufacturing sector have begun to tap into the potential of big data analytics to gain an edge in their markets. Companies in the manufacturing sector can gain a significant competitive advantage by strategically utilizing big data analytics to uncover profound insights that have the potential to significantly enhance their capabilities in product innovation.